ANALISIS TEKNIK DAN IDEOLOGI TERJEMAHAN PADA NOVEL LEAP OF FAITH OLER DANIELLE STEEL DAN PURI KENAN GAN OLEH KATHLEEN S. W. - Edward, Edward (Universitas Lancang Kuning, 2014)
This is a research about an analysis of technique and ideology of translating of Leap of Faith by Danielle Steel and Puri Kenangan byKathleen.S. W The aims of this research are to identify the translation techniques applied by the translator in translating the novel and to analyze the translation ideology. The method in this study is descriptive qualitative using content analysis approach. The source of the data was taken from the English version novel